Chemical proteomics tracks virus entry and uncovers NCAM1 as Zika virus receptor - Mayank Srivastava (Nature Portfolio, 2020)
The mechanism underlying the cellular entry of Zika virus is not fully understood. Here, the authors use a chemically modified virus and time-resolved proteomics to capture interacting host proteins during virus entry and identify NCAM1 as a ZIKV receptor.